2018
DOI: 10.2196/mental.9814
|View full text |Cite
|
Sign up to set email alerts
|

Using Facebook for Improving the Psychological Well-Being of Individuals Experiencing Homelessness: Experimental and Longitudinal Study

Abstract: BackgroundWeb-based social networks are a powerful communicative element and their use is increasingly widespread. Persons living in extreme social exclusion such as individuals experiencing homelessness can benefit from the positive elements of communication and relationship associated with social networking sites.ObjectiveThis study aimed to suggest the comparison of a Facebook training course and an office software course and their effect on psychological well-being in a group of individuals experiencing ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
(43 reference statements)
2
11
0
1
Order By: Relevance
“…Social connectedness, evident in five studies, describes the potential of the mobile phone to maintain social connections [ 23 , 26 , 29 , 31 , 34 ]. Adkins et al [ 23 ] found that participants (homeless youth) predominantly used their phone for communication with friends and family via text and calls.…”
Section: Resultsmentioning
confidence: 99%
“…Social connectedness, evident in five studies, describes the potential of the mobile phone to maintain social connections [ 23 , 26 , 29 , 31 , 34 ]. Adkins et al [ 23 ] found that participants (homeless youth) predominantly used their phone for communication with friends and family via text and calls.…”
Section: Resultsmentioning
confidence: 99%
“…Second, for service providers working with individuals experiencing homelessness requires an appreciation of how to reach them physically and digitally. Common platforms, such as social media, might be a particularly effective way to stay connected, especially among youth populations, and can be an effective tool for introducing interventions [32]. Lastly, although early work has demonstrated that DMH interventions are liked and used, they have failed to establish clinical effectiveness [30••].…”
Section: Individuals Experiencing Homelessnessmentioning
confidence: 99%
“…Their starting point was the use of information and communication technologies, more specifically, the use of social networking sites by homeless people, and they used Facebook and four scales measured at different points. The findings of this study indicate that Facebook as an essential element that can improve the psychological well-being and socialization of the homeless (Calvo and Carbonell, 2018). Hussain et al (2019) used four questionnaires and an eyetracking methodology to study social networking site (Facebook) use and its relation to different indicators of well-being (mental well-being, depression, anxiety, stress, and self-esteem).…”
Section: Well-being Research Through the Collection Of Social Media Datamentioning
confidence: 98%
“…Results showed a relation between Facebook addiction and impoverished well-being in terms of impaired general health, decreased sleep quality, or higher perceived stress (Atroszko et al, 2018). Calvo and Carbonell (2018) designed an experimental and longitudinal study aimed at increasing the well-being of individuals experiencing homelessness. Their starting point was the use of information and communication technologies, more specifically, the use of social networking sites by homeless people, and they used Facebook and four scales measured at different points.…”
Section: Well-being Research Through the Collection Of Social Media Datamentioning
confidence: 99%